Does Herbal and/or Zinc Dietary Supplementation Improve the Antioxidant and Mineral Status of Lambs with Parasite Infection? - Klaudia Čobanová; Zora Váradyová; Ľubomíra Grešáková; Katarína Kucková; Dominika Mravčáková; Marián Várady (MDPI AG, 2020)
This study was conducted to evaluate the effect of feed supplementation with a medicinal herbs mixture (Hmix) and organic zinc (Zn), alone or in combination, on the antioxidant responses and mineral status of lambs infected with the gastrointestinal nematode parasite Haemonchus contortus. A total of 24 experimentally infected lambs were randomly allocated to 1 of 4 dietary treatments (n = 6). The diets included an unsupplemented control diet (CON) and the CON further supplemented with Hmix, Zn, or both Hmix + Zn. Antioxidant enzymes activities, lipid peroxidation, total antioxidant capacity (TAC) and microelement (Zn, Cu, Fe, Mn) concentrations were analyzed in serum, liver, kidney, and intestinal mucosa. Zinc treatment elevated the superoxide dismutase activities in the duodenal mucosa and ileal TAC. Intake of Hmix resulted in higher kidney and ileal catalase activity and also influenced the TAC of the liver and intestinal mucosa. The inclusion of Hmix or Zn alone into the diet increased glutathione peroxidase activity in the blood, liver and duodenal mucosa. Tissue mineral uptake was not affected by herbal supplementation. Organic Zn intake increased the serum and liver Zn levels and influenced the Cu concentration in duodenal mucosa. Dietary supplementation with Hmix and/or Zn might promote the antioxidant status of lambs infected with Haemonchus spp.